Investigation of the phase change mechanism of Ge6Sn2Sb2Te11. (15th June 2018) - Koch, Christine; Dankwort, Torben; Hansen, Anna-Lena; Esters, Marco; Häußler, Dietrich; Volker, Hanno; von Hoegen, Alexander; Wuttig, Matthias; Johnson, David C.; Bensch, Wolfgang; Kienle, Lorenz
Abstract: Thin films of Ge6 Sn2 Sb2 Te11 were synthesized and compared to the well-known unsubstituted phase change material (PCM) Ge8 Sb2 Te11 . In situ X-ray diffraction (XRD) and temperature dependent sheet resistance measurements evidenced a significant decrease of the phase change temperature from 144 °C for Ge8 Sb2 Te11 to 112 °C for Ge6 Sn2 Sb2 Te11 . The resistance measurements also revealed an intermediate step during the phase change. Detailed in situ transmission electron microscopy (TEM) and (XRD) investigations on structural ordering phenomena suggest that this intermediate step is associated with the disorder of structural vacancies on the cationic sites stable up to 130 °C. Annealing the sample beyond 130 °C leads to a subsequent ordering of vacancies and thus to the formation of a metastable primitive trigonal phase with vacancy layers. At ∼240 °C - ∼300 °C, a transition to the stable phase is observed. For the first time, an in plane movement of bi-layer defects is observed by in situ TEM as a result of a self-ordering mechanism. These findings represent new insights into the transition process on the nanoscale and suggest that tin substituted PCMs may represent promising candidates for multi-level data storage applications. Graphical abstract: Image 1